Blood Safety Projects in Azad Jammu & Kashmir: Review of the Strategic Process - Gilani, Irum; Kayani, Ziyad Afzal (International Journal of Pathology, 2018)
AbstractAccess to safe blood underpins the achievement of health-related Millennium Development Goals (MDGs). SWOTanalysis of the Azad Jammu & Kashmir (AJK) blood safety projects has been carried out to determine strategicdirection in scaling up the modern blood transfusion service (BTS). Between 2003 and 2012, one blood safety projecthas been successfully completed in AJK with the second one being implemented. Currently, modern BTS is nestedwithin still dominant traditional laboratory-based blood banking system. Insight into the implementation of theblood safety projects warrants integration of the modern BTS into healthcare system as a cross-cutting service.There is an urgent need to address challenges in ensuring universal access to safe blood in rural areas of AJK.